An Analysis of Factors Influencing Participation of Men Fertilizer Age Couples to Acceptors of Mop (Male Operating Methods) Contraception - Winda Nur Musfiroh Agustin; Ervi Husni; Ani Media Harumi; Erwin L. Rimban; Joylyn L. Mejilla (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Vasectomy or MOP is a long-term contraceptive intended for men which can be a form of husband participation in contraception and family planning so that family planning is not only the wife's obligation. Until now, there is still a lack of male participation in taking MOP Contraception, as stated in the results of the Family Health Profile survey conducted by the BKKBN in 2019 in the Indonesia Health Profile in 2019 the MOP target is 8.77% and the achievement is very far from the target, which is only 0, 5%. (RI, 2019). This study was conducted to identify Knowledge, Attitudes and Support of Childbearing age Men's Wives in Jati Village, and to determine the effect of Wife's knowledge, attitudes and support on the participation of Childbearing age Men in the use of MOP contraception. The type of research carried out is observational with analytical survey research methods and cross sectional approach with a population of 405 people and a sample of 134 Childbearing age Men. The sampling technique was cluster random sampling. The dependent variable in this study was the participation of Childbearing age Men, while the independent variables were attitudes, knowledge, and wife's support. Bivariate analysis used is Chi Square with 0.05, Multivariate analysis used is Multiple Logistics Regression. Results: Most (72.4%) Childbearing age Men have less knowledge, Almost all (78.4%) Childbearing age men have a negative attitude towards MOP contraception, and Almost all Childbearing age Men (84.3%) do not receive the support of their wives in participating in using MOP contraception. The results of the analysis test showed that there was an influence of knowledge with the participation of male pus in the use of MOP contraception (P value 0.000) , there was an effect of male pus attitude with participation in the use of MOP contraception (P value 0.025) and there was an effect of wife's support with the participation of male pus in the use of MOP contraception. (P value 0.020). The most influential factor is wife's support with an OR value of 21.712. There is an effect of Wife's Knowledge, Attitude and Support with the participation of Childbearing age Men in the use of MOP contraception.